Serviço e comunidade, vetores para a formação em saúde: o curso de medicina da Uniderp - Cabral, Paulo Eduardo; Machado, Jose Lucio Martins; Machado, Valéria Menezes Peixeiro; Pompílio, Maurício Antonio; Vinha, Joaquim Miguel; Ayach, Wilson; Mattos, Maria Cristina Iwama De [UNESP] (Associação Brasileira de Educação Médica, 2008)
This paper relates the planning, implantation and implementation process of the Inter-institutional Program for University-Health Service-Community Interaction (Pinesc), a partnership between the university, the city council of Campo Grande and the Local Health System aimed at producing a longitudinal curriculum module of community based education (CBE and Come), developed over eight semesters of the medical course of the Universidade para o Desenvolvimento do Estado e da Região do Pantanal (Uniderp, Anhanguera, MS, Brazil). This report tells the history of the implementation of the program, its strengths, difficulties and unforeseen developments besides approaching some operational aspects.

Este trabalho registra o processo de concepção, implantação e implementação do Programa Interinstitucional de Interação de Ensino, Serviço, Comunidade (Pinesc), uma parceria entre a universidade e a Prefeitura Municipal de Campo Grande, visando à realização de módulos curriculares longitudinais de ensino baseado na comunidade, desenvolvidos em oito semestres letivos do curso de medicina da Universidade para o Desenvolvimento do Estado e da Região do Pantanal (Uniderp, Anhanguera, MS). O relato inlcui o histórico, com seus pontos fortes e dificuldades, além de desdobramentos ão previstos, bem como aspectos operacionais do programa.
The health system and the community as vectors for the preparation of health professionals: the medical course at Uniderp
Keywords: Medical Educations; Problem-based learning; Community-institucional Relations; Health services; Family health; Single health system; Educação médica; Aprendizagem baseada em experiência; Extensão comunitária; Serviços de saúde; Saúde da família; Sistema Único de Saúde